The End a content analysis of the Philippine Daily Inquirer's coverage on the ending of the Vizconde massacre trial at the Lower Court - Balquiedra, Barnard Carlos
The study qualitatively and quantitatively analyzed the Philippine Daily Inquirer's (PDI) coverage of the Vizconde massacre trial at the lower court 31 days before the promulgation and 31 days thereafter. In the qualitative analysis, the researcher found that the articles of the PDI that came out during the Pre-Verdict period suggested more emphatically that the suspects were guilty based on the phrases or words used by the reporters. This was seen from the way some articles established the image of the suspects as drug users. It also mentioned Hubert Webb as a "villain we love to hate due to public perception that he is a spoiled, wealthy and politically influential young man who will most certainly escape liability from this crime" (PDI, January 6, 2000). There were also speculations already of a guilty verdict weeks before the promulgation. Meanwhile, the Post-Verdict articles of the PDI showed that the daily was supportive of the judge's decision based on the phrases or words used by the reporters that suggest so. PDI was consistent in its reporting because after implying during the Pre-Verdict stage that the suspects were guilty, after their conviction the articles that came out supported the judge's decision. The researcher also discovered that the foci of the articles in both the Pre= and Post-Verdict periods were very similar. Both periods mainly focused on the economic status or power of the accused/convicts, and on the protagonists of the case, most specifically Hubert Webb and Lauro Vizconde. The quantitative analysis showed that the PDI overwhelmingly paid more attention on the Vizconde massacre case during the Post-Verdict period that during the Pre-Verdict period, based on the number of news articles, photographs, cartoons, opinion columns, etc. published related to the Vizconde massacre case. The researcher also found that the Pre- and Post-Verdict periods had the same slant. They both tended to be negative on the defense side. Six out of the 13 articles that came out during the Pre-Verdict period in the PDI suggested that the suspects were guilty. On the other hand, the Post-Verdict period showed that 13 out of the 29 articles that came out after the verdict tended to support the judge's decision. This means that the PDI has been consistent with its reporting on the Vizconde case. In fact, the PDI did not have a change of heart in its manner of reporting despite the long trial, evidences presented, witnesses' testimonies, new developments that cropped up, etc. that buffeted the newspaper's initial stand. At the same time, the findings showed that the PDI did not change its focus before and after the decision. During the Pre-Verdict stage, the findings showed that 8 out of the 13 articles fell under Theme 4 which indicated that the focus of the PDI was on the case itself. After the verdict, its news articles focused on the Theme 3. Theme 3 indicated that the focus was on the convicts' lives after the verdict. This was the theme of 10 1/2 out of the 29 news articles of the PDI articles. The results indicated that the PDI's main concern both during the Pre- and Post-Verdict periods was on the resolution of the case more than anything else. During the Pre-Verdict period they mostly reported on the developments of the case and the arguments of the lawyers. On the other hand, during the Post-Verdict period they reported mostly on the legal plans of the convicts and their lawyers and the search for the two other missing suspects. All of these pointed to one direction, and that was the resolution of the case.